Reexamining Student-Athlete GPA: Traditional vs. Athletic Variables - Johnson, James E.; Wessel, Roger D.; Pierce, David (Journal of Intercollegiate Sport, 2010)
A sample of 674 first-year student-athletes at a midsize Midwestern university were examined each year over a five-year period (2004–2008) to determine if athletic variables were powerful enough to be used in conjunction with traditional predictors of college success to predict GPA. The four specific athletic variables unique to student-athletes (i.e., sport, coaching change, playing time, team winning percentage), were hypothesized to be as predictive as traditional variables. Pearson correlations revealed student-athletes were more likely to earn a high first-year GPA if they were female (r = .35), Caucasian (r = -.33), scored well on standardized tests (r = -.47), had a respectable high school GPA (r = .64), were ranked high in their graduating high school class (r = -.58), had a relatively large high school graduating class (r = .15) were not undecided about major (r = -.11), were not a member of a revenue sport (r = .33), and earned a considerable amount of playing time in their first year (r = -.15). Least squares linear regression demonstrated the traditional variables of gender (B = .16), race (B = -.26), standardized test scores (B = .03), high school GPA (B = .41), high school rank (B < -.01), and size of high school graduating class (B < .01) were most influential in predicting first-year student-athlete GPA.